Penguatan Kompetensi Pendidik melalui Pelatihan Penggunaan Kecerdasan Buatan (AI) dan Media TIK dalam Rancangan Pembelajaran yang Efektif - Suherman, Suherman; Aziz, Saddam Al; Dwina, Fitrani; Rani, Maulani Meutia (EDUPEDIA Publisher, 2025)
Educators must be able to design interactive learning to develop their pedagogical competencies in the 21st century. One of the efforts that can be made is utilizing technology in mathematics learning. This Community Service activity aims to provide training and to discover educators' perceptions of training using Artificial Intelligence and ICT Media in learning design. This training was conducted on November 13-14, 2024, at SMP Negeri 1 Solok. The training participants were 30 Solok City Mathematics Teacher Working Group (MGMP) members. The stages of this activity were initiation, preparation, implementation, and evaluation. Data was collected by distributing a questionnaire using a 1-4 Likert scale. The results showed that after participating in the training, the participants were delighted and enthusiastic, and the training provided could be applied in mathematics learning. The average score for educators' perceptions of this training activity was 88.09%, which falls into the